1981
DOI: 10.1111/j.1365-2621.1981.tb04485.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Content of Beef Bone Marrow and Mechanically Deboned Meat

Abstract: Marrow from cervical, lumbar and femur bones-of 5 steers and 5 cows fed only on native range (grass fed) and 5 steers and 5 cows fed a finishing ration (grain fed) was analyzed for cholesterol content. The cholesterol content of the marrow was significantly different when diet or anatomical locations were compared. Bovine marrow from grass-fed animals averaged 119.6 mg/lOOg and marrow from grain-fed animals averaged 150.6 mg/lOOg marrow. The cholesterol content of marrow from the cervical, lumbar, and femur wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Other stationary phases that have been used for cholesterol analysis by GC are OV‐17 (phenyl methyl siloxane), SE‐52 (methyl phenyl siloxane), Apiezon L (hydrocarbon grease), SP‐2401 (trifluoropropyl methyl siloxane), and OV‐101 (methyl siloxane) (Heftmann 1976; Fenton 1992). Similarly, Kunsman and others (1981) and Ryan and Gray (1984) used a nonpolar stationary phase (SP‐2100, 100% dimethyl polysiloxane) to coat Supelcoport packed into a glass column for cholesterol determination. Cholesterol is typically classified as a nonpolar compound; therefore, a nonpolar stationary phase has been employed.…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other stationary phases that have been used for cholesterol analysis by GC are OV‐17 (phenyl methyl siloxane), SE‐52 (methyl phenyl siloxane), Apiezon L (hydrocarbon grease), SP‐2401 (trifluoropropyl methyl siloxane), and OV‐101 (methyl siloxane) (Heftmann 1976; Fenton 1992). Similarly, Kunsman and others (1981) and Ryan and Gray (1984) used a nonpolar stationary phase (SP‐2100, 100% dimethyl polysiloxane) to coat Supelcoport packed into a glass column for cholesterol determination. Cholesterol is typically classified as a nonpolar compound; therefore, a nonpolar stationary phase has been employed.…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 99%
“…Osman and Chin (2006) used a high‐temperature column and reported that the cholesterol peak was sharp. Even with packed columns, the separation and quantification of free cholesterol were found to be satisfactory (Kovacs and others 1979; Kunsman and others 1981; Ryan and Gray 1984). Kovacs and others (1979) found no significant difference between recoveries of the cholesterol TMS‐derivative and the free cholesterol.…”
Section: Cholesterol Analytical Methods In Meat and Poultry Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSM is not without controversy, however. Most reports indicate that MSM is lower in protein and higher in fat and cholesterol th,an conventional meats Field, 1976, Kolbye et al, 1977;Arasu et al, 1981;Kunsman et al, 1981). Furthermore, there are indications that MSM may be higher in nucleic acids than ground muscle tissue (Arasu et al, 1981).…”
Section: Mechanicalmentioning
confidence: 99%
“…Ruminant brain and marrow contains around 2037mg /100 g [129] and 119-6mg/ 100g [130] cholesterol respectively. We believe, that such amounts would entail a significant increase in cholesterol and metabolites in early human sterol output, reflecting dietary changes.…”
Section: Discussionmentioning
confidence: 99%